Neuronal Migration from the Forebrain to the Olfactory Bulb Requires a New Attractant Persistent in the Olfactory Bulb - Liu, Guofa (J Neurosci, 2003)
Interneurons in the olfactory bulb (OB) are generated not only in the developing embryo but also throughout the postnatal life of mammals from neuronal precursor cells migrating from the anterior subventricular zone (SVZa) of the mammalian forebrain. We discovered that the OB secretes a diffusible activity that attracts these neuronal precursor cells. The attractive activity is present in specific layers in the OB, including the glomerular layer but not the granule cell layer. The attractive activity and the neuronal responsiveness persist from embryonic through neonatal to adult stages. Removal of the rostral OB significantly reduces SVZa migration toward the OB, an effect that can be rescued by a transplant of the OB but not by that of the neocortex. The activity in the OB is not mimicked by the known attractants. These results provide an explanation for the continuous migration of SVZa neurons toward the OB, demonstrate an important role of the OB in neuronal migration, and reveal the existence of a new chemoattractant.